Subcutaneous Zygomycosis Treated With Ketoconazole - Roy Alok Kumar; Sarkar Jyotirindra Nath; Maiti Prasanta Kumar (Wolters Kluwer Medknow Publications, 2000)
A six year old female child presented with indolent nontender swellings on both buttocks and loins, was provided by histropathological and mycological examinations, to be suffering from subcutaneous zygomycosis. Being intolerant to potassium iodide, she was put on and responded to ketoconazote therapy.